Trade Unions in the European Union. - Waddington, Jeremy; Müller, Torsten; Vandaele, Kurt. (Brussels : P.I.E. - Peter Lang SA Éditions Scientifiques Internationales, 2023)
This book offers a comprehensive comparative overview of the development, structure, and policies of trade unions in all the 27 Member States of the EU from 2000 to 2020. It presents an in-depth analysis of the neoliberal challenges facing these organizations and their strategic and policy responses.
Chapter 16 Trade unions in Italy: Pluralism and resilience (Salvo Leonardi, Roberto Pedersini) -- Chapter 17 Latvia: Trade unions with the potential to escape marginalization (Elza Ungure) -- Chapter 18 Lithuania: Trade unions still see light at the end of the tunnel (Inga Blažienė) -- Chapter 19 Trade unions in Luxembourg: Residual institutional strength and declining mobilization capacity (Adrien Thomas) -- Chapter 20 Malta: Trade union resilience in a changing environment (Manwel Debono, Luke Anthony Fiorini) -- Chapter 21 Trade unions in the Netherlands: Erosion of their power base in the stable Polder Model (Paul de Beer, Lisa Berntsen) -- Chapter 22 Poland: Trade unions developing after a decline (Jan Czarzasty, Adam Mrozowicki) -- Chapter 23 Trade unions in Portugal: Between Marginalization and revitalization (Maria da Paz Campos Lima, Reinhard Naumann) -- Chapter 24 Trade unions in Romania: Walking the thin line between politics and the market (Ștefan Guga, Aurora Trif) -- Chapter 25 Trade unions in Slovakia: From politics to bread-and-butter unionism (Marta Kahancová, Monika Uhlerová) -- Chapter 26 Slovenia: From strong trade union movement to uneven de-unionization (Miroslav Stanojević, Andreja Poje, Živa Broder) -- Chapter 27 Spain: Boundaries, roles and changes in trade unionism (Carlos J. Fernández Rodríguez, Rafael Ibáñez Rojo, Miguel Martínez Lucio) -- Chapter 28 Trade unions in Sweden: still high union density, but widening gaps by social category and national origin (Anders Kjellberg) -- Chapter 29 Conclusion: Trade Unions picking up the pieces from the neoliberal challenge (Jeremy Waddington, Torsten Müller, Kurt Vandaele) -- Appendix A1 Indicators relevant to trade unions in the European Union -- Series Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books